Pengaruh Pengetahuan Dewan Terhadap Pengawasan Anggaran pada Sekretariat Dewan Perwakilan Rakyat Daerah Kota Gorontalo - Mahfiza Mahfiza (Al-Buhuts, 2018)
This study aims to determine the effect of the board's knowledge of budget oversight at the Gorontalo City DPRD Secretariat. The method used to analyze the data in this research is simple regression. In testing hypotheses that use regression analysis requires that the data analyzed be at least interval scale data. The results of the study indicate that the knowledge of board members has a significant effect on budget oversight.